The dysregulation of PARP9 expression is linked to apoptosis and DNA damage in gastric cancer cells. - Yating Li; Xing Wang; Xiaolong Liu; Xiangjie Li; Jianling Zhang; Yulan Li (PLoS ONE)
Background Gastric cancer (GC) is a highly malignant gastrointestinal tumor characterized by difficult early diagnosis and poor prognosis. Therefore, it is imperative to explore potential therapeutic targets for gastric cancer. PARP9 is abnormally expressed in a variety of tumors and is associated with tumor cell apoptosis and DNA damage. However, its relationship with GC has not been fully studied. Methods The expression and prognostic significance of PARP9 in gastric cancer (GC) were examined using bioinformatics approaches. Cell lines with either knockdown or overexpression of PARP9 were established through lentiviral transduction, and the role of PARP9 in the malignant phenotypes of GC cells was validated via CCK8 assays, wound healing assays, clonogenic assays, and Transwell migration experiments. Finally, alterations in downstream targets and signaling pathways following changes in PARP9 expression were analyzed through RNA sequencing. Results PARP9 is highly expressed in GC tissues and is associated with poor prognosis. PARP9 knockdown can significantly inhibit the proliferation, invasion and migration of GC cells, and increase the apoptosis and DNA damage of GC cells. The therapeutic process of PARP9 in GC may be realized by synergistic interaction with SOX6 through MAPK signaling pathway. Conclusions Our study reveals a potential link between PARP9 and GC, providing a new target for the treatment of GC.